Unlocking Africa’s Economic Potential: A Comprehensive Analysis of AfCFTA Opportunities for Women and Youth as Workers, Consumers, Producers, and Traders - Nganga, Tabitha (International Journal of Economics, 2025)
Purpose: The African Continental Free Trade Area (AfCFTA) represents a monumental step toward the economic integration of the African continent, aiming to create a single market for goods and services among 55 African Union member states. With an anticipated market of 1.3 billion people and a combined GDP exceeding $3.4 trillion, the AfCFTA holds transformative potential for fostering inclusive and sustainable growth. Central to this transformation is the strategic inclusion of two historically marginalized but economically vital groups: women and youth. This article critically examines the promises and practical pathways through which the AfCFTA can become a driver of inclusive economic empowerment for women and youth. Methodology: Drawing from treaty provisions, policy frameworks such as Agenda 2063, and a range of empirical data, the paper analyzes opportunities across the economic spectrum: as workers, consumers, producers, and traders. It also integrates case studies and comparative insights to underscore the practical realities and innovations shaping gender-responsive trade policies. Findings: Women account for the majority of the informal trade workforce across Africa, while youth represent over 70% of the population under the age of 30. Both groups possess immense economic potential but face significant structural and systemic barriers including limited access to finance, education, infrastructure, and representation in policy decision-making. Unique Contribution to Theory, Practice and Policy: The article offers actionable policy recommendations to national governments, the AfCFTA Secretariat, and civil society. Ultimately, the paper argues that the success of the AfCFTA hinges not only on economic liberalization but on its ability to deliver social transformation—where inclusivity, equality, and empowerment are foundational pillars of Africa’s economic renaissance.